STRATEGI ADAPTIF KEDAI KOPI “COFFEEBREAK” PURWOKERTO DALAM UPAYA MENYONGSONG NEW NORMAL - SITI BAROKAH,; ANISA NUR ANDINA,; ZAHRAH ANGGIANY, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Covid-19 pandemic presents special opportunities and challenges for various industrial sectors. This is not only happening in the State of Indonesia, but also published in other countries in the world. Since the World Health Organization (WHO) announced that the covid19 pandemic is a world pandemic, which has affected consumers in various business sectors. Many business sectors in the Banyumas Regency specifically the Purwokerto region were temporarily closed due to the co-19 pandemic and reopened after conditions were better. Therefore, business efforts are demanded to be able to compile and implement adaptive strategies to welcome the new normal business to continue in the midst of changes in environment that are difficult to predict and can increase sales and achieve all the company's vision and mission. The purpose of this study was to see the extent of the coffee shop's business "Coffeebreak" in compiling and implementing strategies to improve current environmental conditions after the emergence of the co-19 pandemic. The research method used in this research is descriptive qualitative method. The sample in this study was the owner and customer of Purwokerto "Coffeebreak" coffee shop. The results showed that the coffee shop "Coffeebreak" had implemented an adaptive strategy in an effort to meet the new normal.